Comparative study on the development of maize flour based composite bread (Journal of the Bangladesh Agricultural University, 2014)
The study was conducted to develop composite bread with maize flour and also to evaluate the nutritional quality and sensory properties of resulting breads. The results of the proximate analysis showed that wheat and maize flour contain protein 12.56 and 9.08%; fat 0.85 and 1.15%; ash 0.62 and 1.60%; fibre 0.68 and 1.25%; gluten 12.11 and 0.0%, respectively. Breads were produced from composite flour containing 10, 20, 25, 30 and 40% of maize flour and compared with wheat bread for various quality attributes of the developed products. The incorporation of maize flour adversely affected the baking properties and dough expansion but the nutritional quality was improved in case of fiber and energy content. The sensory analysis showed that there was no significant difference between the wheat bread and bread with 10% maize flour. Substitution of 10% maize flour into wheat flour retained much of the nutritional and sensory properties and gave the bread with the good overall acceptability. It was found that volume and specific volume highly positively correlated with taste, texture and overall acceptability but negatively correlated with hardness. The sensory qualities such as hardness and springiness deteriorated during storage with increasing level of maize flour in the breads. DOI: http://dx.doi.org/10.3329/jbau.v11i1.18224 J. Bangladesh Agril. Univ. 11(1): 133-139, 2013